Membrane Trafficking and Subcellular Drug Targeting Pathways - Kumar, Ajay; Ahmad, Anas; Vyawahare, Akshay; Khan, Rehan (Frontiers in Pharmacology, 2020)
The movement of micro and macro molecules into and within a cell significantly governs several of their pharmacokinetic and pharmacodynamic parameters thus governing the cellular response to exogenous and endogenous stimuli. Trafficking of various pharmacological agents and other bioactive molecules throughout and within the cell is necessary for the fidelity of the cells, but has been poorly investigated. Novel strategies against cancer and microbial infections need the deeper understanding of membrane as well as subcellular trafficking pathways and essentially regulate several aspects of the initiation and spread of anti-microbial and anti-cancer drug resistance. Furthermore, in order to maximally enhance the bioavailability and therapeutic efficacy and restrict the unwanted toxicity of pharmacological bioactives, these sometimes need to get functionalized with targeting ligands to regulate the subcellular trafficking enhance localization. The scenario in the recent past for drug targeting primarily focused on targeting tissue components and cell vicinities however it is the membranous and subcellular trafficking system that directs the molecules to plausible locations. The effectiveness of the delivery platforms largely depends on their physicochemical nature, intracellular barriers, biodistribution of the drugs, pharmacokinetics and pharmacodynamics paradigms. Most subcellular organelles possess some peculiar characteristics by which membranous and subcellular targeting can be manipulated like – negative transmembrane potential in mitochondria, intraluminal delta pH in a lysosome and many others. There exist many specialized methods which positively promote the subcellular targeting and restricts off-targeting of the bioactive molecules. Recent advancements in designing the carrier molecules enable the handling of membrane trafficking to assist the delivery of active compounds to subcellular localizations. This review aims to cover membrane trafficking pathways which regulate the transport of active molecule to the subcellular locations, associated subcellular pathways and the role of design of delivery system.